Coat/Tether Interactions—Exception or Rule? - Schröter, Saskia; Beckmann, Sabrina; Schmitt, Hans Dieter (Frontiers in Cell and Developmental Biology, 2016)
Coat complexes are important for cargo selection and vesicle formation. Recent evidence suggests that they may also be involved in vesicle targeting. Tethering factors, which form an initial bridge between vesicles and the target membrane, may bind to coat complexes. In this review, we ask whether these coat/tether interactions share some common mechanisms, or whether they are special adaptations to the needs of very specific transport steps. We compare recent findings in two multisubunit tethering complexes, the Dsl1 complex and the HOPS complex, and put them into context with the TRAPP I complex as a prominent example for coat/tether interactions. We explore where coat/tether interactions are found, compare their function and structure, and comment on a possible evolution from a common ancestor of coats and tethers.